Temuan Klinis Oral pada Pasien HIVAIDS di Poli Penyakit Mulut RSUD Kota Tangerang - Mersil, Sarah; Miyuri Areta; Rani Handayani (Lembaga Penelitian Universitas YARSI, 2025)
Background: Human Immunodeficiency Virus (HIV) is a type of virus that attacks white blood cells and causes a decrease in the human immune system. The route of HIV transmission can be through sexual intercourse, shared syringe use, transmission through the placenta from HIV-positive mothers to children, and transfusion of blood infected with the virus. According to WHO data, about 39 million people are infected with HIV by the end of 2022. Oral manifestations are the initial symptoms in 30-80% of HIV-infected people and can be used to detect HIV/AIDS early. Objective: This study aims to identify oral clinical finding in HIV/AIDS patients at oral disease clinic of RSUD Kota Tangerang. Methods: This research was descriptive analysis using cross- sectional study design from 97 electronic medical records of HIV/AIDS patients at the Oral Medicine Clinic of RSUD Kota Tangerang. The data collected included the diagnosis of oral cavity findings. Results: The results showed that the three highest percentages related to oral manifestations found were chronic gingivitis (26.7%), then oral candidiasis (21.1%), coated tongue (16.2%), cheilitis (9.7%) and apthous like ulcer (6.5%). Conclusion: In HIV/AIDS patients at the Oral Medicine Clinic, there are many oral manifestations that vary.